Outcomes of lung transplantation from SARS-CoV-2 positive donors during the Omicron wave - Sonya M. Kothadia; Cameron R. Wolfe; Arthur W. Baker; Katherine A. Young; John M. Reynolds; Matthew G. Hartwig; Amanda Rooney; Madeleine R. Heldman (JHLT Open)
Early observations of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) transmission via lung transplantation have led to frequent discard of lungs from donors with positive SARS-CoV-2 tests. We compared survival between lung transplant recipients (LUTRs) with SARS-CoV-2 (+) (n = 11) and SARS-CoV-2 (-) donors (n = 192) transplanted from January 30, 2022 to March 31, 2024. Three of the 11 SARS-CoV-2 (+) donors had positive lower respiratory tract (LRT) tests. Two of their 3 recipients developed post-transplant SARS-CoV-2 infections, including one LUTR who died 11 days post-transplant. LUTRs with SARS-CoV-2 (+) donors had higher 30-day mortality (2/11 [18.2%] vs 7/192 [3.6%], p = 0.02), but there was no significant difference in 1-year mortality (2/11 [18.2%] vs 27/192 [14.1%], p = 0.56). Only 3 (27%) LUTRs with SARS-CoV-2 (+) donors developed acute cellular rejection in the first post-transplant year, and none were diagnosed with chronic lung allograft dysfunction. These findings support consideration of SARS-CoV-2 (+) lung donors, especially when LRT testing is negative.